V2Va +: An Efficient SystemVerilog & Verilog-to-Verilog-A Translator for Accelerated Mixed-Signal Simulation - Chao Wang; Yicong Shao; Jiajie Huang; Wangzilu Lu; Zhiwen Gu; Longfan Li; Yuhang Zhang; Jian Zhao; Wei Mao; Yongfu Li (IEEE Open Journal of Circuits and Systems)
This paper introduces a streamlined SystemVerilog & Verilog-to-Verilog-A (V2Va +) translation tool that automates the conversion of synthesizable SystemVerilog and Verilog code into Verilog-A code, enabling concurrent simulation of analog and digital circuits. Through a set of mapping rules, V2Va + facilitates mixed-signal simulations in an analog environment, negating the requirement for a separate mixed-signal simulation engine and overcoming multiple types of EDA licensing obstacles. The V2Va + translation tool comprises two integral components: a parser function, tasked with extracting information from SystemVerilog and Verilog files, and a Verilog-A generator, responsible for generating corresponding Verilog-A code. V2Va + excels in handling complexity, ensuring accuracy, and improving efficiency. It effectively manages a wide range of design complexities, maintains functional consistency during translation, and significantly reduces simulation time, achieving speed-ups of over $2{× }$ . These strengths underscore its significant impact and applicability in the domain of circuit design.